2019
DOI: 10.22270/ajprd.v7i1.469
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Diabetic Effects of Some Medicinal Plants in Experimental Animals: A Review

Abstract: Diabetes is a chronic endocrine disease with global prevalence and increasing incidence. Diabetes presents with a major health issue in all age groups in the present times owing to its multisystem involvement and serious complications. In spite of drug development and therapeutic interventions, successful treatment of diabetes still remains a challenge and worldwide research is focused on finding alternative modalities. By conducting sizable amount of analytical work, numerous traditional medicines have been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Results indicated that AMAE attenuated body weight gain as compared HFD control group were in agreement with who found that AM extracts attenuated body weight gain and exhibited anti-obesity activity may due to decrease fat pad mass, by reduced adipocyte differentiation or by decreasing adipocyte hypertrophy in high fat diet induced obese rats. Also, Maqbool et al, (2019) and Siddiqui et al, (2019) reported that Aegle marmelos is effective in restoration the body weight to normal levels.…”
Section: Resultsmentioning
confidence: 96%
“…Results indicated that AMAE attenuated body weight gain as compared HFD control group were in agreement with who found that AM extracts attenuated body weight gain and exhibited anti-obesity activity may due to decrease fat pad mass, by reduced adipocyte differentiation or by decreasing adipocyte hypertrophy in high fat diet induced obese rats. Also, Maqbool et al, (2019) and Siddiqui et al, (2019) reported that Aegle marmelos is effective in restoration the body weight to normal levels.…”
Section: Resultsmentioning
confidence: 96%
“…According to new study, the leaf juice from A.Marmelos was effective in diabetes mellitus, which may be attributed to the presence of bioactive components such as aegelin, scopoletin, and sitosterol in the leaves. 14,15…”
Section: Antihyperglycemic Activitymentioning
confidence: 99%
“…[87] The hexane fraction of N. sativa seeds' methanol extract revealed substantial anti-inflammatory activity by inhibiting nitric oxide release in lipopolysaccharide-stimulated RAW 264.7 macrophages, with an IC50 value of 6.20 μg/mL (Pichette et al, 2012). [88][89][90] A clinical trial study was conducted as prospective and double blind with descriptive analytic to investigate the antiinflammatory property of N. sativa in patients with symptoms of allergic rhinitis. 66 patients (placebo and case) with allergic rhinitis were involved and exposed to N. sativa oil.…”
Section: Hepatoprotective Actionmentioning
confidence: 99%